Pendampingan Kelompok Belajar Anak Usia Dini Di Kampung Mulyasari, Desa Sukamulya, Kabupaten Bogor - Agustina, Riza (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2022)
The absence of a permanent school in Sukamulya Village, Mulyasari, Bogor, has caused the children not to get a proper education. This condition has encouraged us to carry out mentoring activities for early childhood children. This assistance is carried out using an action research approach which consists of four stages, namely planning, implementing actions, observing and evaluating, and finally reflecting. The mentoring activities that we carry out are: First, the use of the drill method in coloring activities and collage materials. Children are trained to manage fine art by arranging and gluing parts of natural materials, artificial materials and used materials on drawing paper to produce unique and interesting arrangements. Second, the use of the storytelling method to convey or present learning material orally in the form of stories from teachers to children. This method aims to provide or instill social values, morals, non-violence, and social environment. This assistance received a positive response, as evidenced by the enthusiasm of the children in participating in the activity from start to finish. Activities of early childhood children who initially played more, are now accompanied by learning. Children in Mulyasari village can also experience learning like other kindergarten or PAUD institutions. One of the limitations in this mentoring activity is the lack of reading books for children.